Reconhecimento de imagens de marcas de gado utilizando redes neurais convolucionais e máquinas de vetores de suporte - Santos, Carlos Alexandre Silva dos (2017)
The automatic recognition of cattle branding is a necessity for government agencies responsible for this activity. In order to improve this process, this work proposes an architecture which is able of performing the automatic recognition of these brandings. The proposed software implements two methods, namely: Bag-of-Features and CNN. For the Bag-of-Features method, the SURF algorithm was used in order to extract points of interest from the images. We also used K-means clustering to create the visual word cluster. The Bag-of-Features method presented a overall accuracy of 86.02% and a processing time of 56.705 seconds in a set containing 12 brandings and 540 images. For the CNN method, we created a complete network with five convolutional layers, and three layers fully connected. For the 1st convolutional layer we converted the input images into the RGB color for mat. In order to activate the CNN, we performed an application of the ReLU, and used the maxpooling technique for the reduction. The CNN method presented 93.28% of overall accuracy and a processing time of 12.716 seconds for a set containing 12 brandings and 540 images. The CNN method includes six steps: a) selecting the image database; b) selecting the pre-trained CNN model; c) pre-processing the images and applying the CNN; d) extracting the features from the images; e) training and classifying the images using SVM; f) assessing the classification results. The experiments were performed using the cattle branding image set of a City Hall. Metrics of overall accuracy, recall, precision, Kappa coefficient, and processing time were used in order to assess the performance of the proposed architecture. Results were satisfactory. The CNN method showed the best results when compared to Bag-of-Features method, considering that it was 7.26% more accurate and 43.989 seconds faster. Also, some experiments were conducted with the CNN method for sets of brandings with a greater number of samples. These larger sets presented a overall accuracy rate of 94.90% for 12 brandings and 840 images, and 80.57% for 500 brandings and 22,500 images, respectively.